Media Pembelajaran Blackbox dan Model Problem Based Learning: Inovasi Tingkatkan Pembelajaran Matematika SD - Dis Tri Prihatini; Zulqoidi R. Habibie; Aldino Aldino (CV. Master Literasi Indonesia, 2025)
This research is a classroom action research conducted in 2 cycles with four stages each cycle including planning, implementation, observation, and reflection, with the aim of improving the process and results of mathematics learning through the application of the Problem Based Learning model assisted by Blackbox media, Descriptive statistical data analysis techniques, One Sample T Test, and Descriptive. The results of the study showed an increase in which from cycle 1 for the student learning process of 79.63% and learning outcomes of 29%, while cycle 2 the student learning process was 85.18% and learning outcomes of 88%. So it can be concluded that there is an increase in both the process and learning outcomes through the application of the Problem Based Learning model assisted by Blackbox media in the mathematics subject of class III SDN 088/II Sungai Mengkuang.